2016
DOI: 10.1007/s10237-016-0839-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flowing RBCs on adhesion of a circulating tumor cell in microvessels

Abstract: Adhesion of circulating tumor cells (CTCs) to the microvessel wall largely depends on the blood hydrodynamic conditions, one of which is the blood viscosity. Since blood is a non-Newtonian fluid, whose viscosity increases with hematocrit, in the microvessels at low shear rate. In this study, the effects of hematocrit, vessel size, flow rate and red blood cells (RBCs) aggregation on adhesion of a CTC in the microvessels were numerically investigated using dissipative particle dynamics. The membrane of cells was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…Their results indicated that cells with deformations roll much slower and are relatively more stable than those without deformation in shear flow, facts consistent with the experimental findings (9,10). Since then, numerous simulation studies continue to address the process of cell deformation during cellular adhesion (11)(12)(13)(14)(15)(16).…”
Section: Introductionsupporting
confidence: 72%
“…Their results indicated that cells with deformations roll much slower and are relatively more stable than those without deformation in shear flow, facts consistent with the experimental findings (9,10). Since then, numerous simulation studies continue to address the process of cell deformation during cellular adhesion (11)(12)(13)(14)(15)(16).…”
Section: Introductionsupporting
confidence: 72%
“…However, some experiments [ 23 25 ] have shown that the soft CTCs are more likely to extravasate from the circulation, because the soft CTCs have a large contact surface with the vascular wall and thus have a higher possibility of adhesion than the rigid CTCs. Recently, some simulation work [ 26 , 27 ] has also favored the latter conclusion.…”
Section: Introductionmentioning
confidence: 94%
“…A stochastic adhesive model was developed by Hammer and Apte [ 28 ], which has been widely used to theoretically and numerically investigate the adhesion of various cells, certainly including the CTCs [ 27 ]. The model proposed that the cell adhesion is attributed to the dynamic association and dissociation between the receptors on the cell and the ligands on the vessel wall.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased cell deformability and increased cell volume in T2DM have shown significant implications for microcirculatory alterations. Computational modeling and simulations help in predicting how RBCs behave in shear flow and providing insights into how viscous flow transforms RBC shapes, and vice versa, how deformed RBCs distort the surrounding flow (24,42,43,(78)(79)(80)(81)(82). Here, in order to address the effects of cell elasticity and shape on the biorheological behavior of individual T2DM RBCs, we investigate the dynamic behavior of T2DM RBCs in a microfluidic channel with constriction.…”
Section: Rheological Properties Of T2dm Rbcs In Shear Flowmentioning
confidence: 99%